Early Marriage and Mental Health: A Case-Control Study of Psychological Outcomes - Hartanti, Monica Dwi; Adiningsih, Setyo; Isnawati, Rina; Poetranto, Anna Lystia; Puetri, Nona Rahmaida; Desem, Muhammad Ibrahim; Saputra, Fery Surahman; Hidayat, Yance (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Background: Bengkulu Province is one of the provinces in Indonesia that has the greatest incidence of early marriages. It is well knowledge that women in this province are more likely to be victims of crimes such as domestic violence, problems during pregnancy, and even death during childbirth. It is possible for moms who enter into early marriages to develop psychiatric illnesses, which can not only be a forerunner to a variety of health impacts in later life but also have the potential to have a detrimental impact on their children and families. Objective: This study seeks to examine the factors related to psychological issues in early marriage in Bengkulu Province. Method: For this investigation, a case-control study design is utilized, and the groups are separated according to geography. The group under consideration is a rural region with a greater rate of marriages occurring at a younger age. The control group, on the other hand, is urban. One hundred and thirty-seven mothers who had been married off at a young age made up the study's target sample. Each of the groups had 137 responses, ensuring that the ratio was one to one. The research instrument that was utilized in this study was a questionnaire, and the application Stata 14 was utilized for both univariate test analysis and logistic regression. Results: The husband's perspective (OR: 6.5; 95% CI: 2.1–13.2; P-value: less than 0.001) and societal stigma (OR: 6.4; 95% CI: 1.1–13.4; P-value: less than 0.001) were significant factors associated with elevated stress levels, correlating with the highest scores. The control group comprised quality of life (OR: 6.7; 95% CI: 2.1-11.9; P-value: 0.001) and family support (OR: 6.2; 95% CI: 2.1-11.4; P-value: less than 0.001). In the depressed symptoms component, the variables that exhibited a significant conclusive association with the highest score were the spouse's perception (OR 6.4; 95% CI: 2.1-11.7; P-value: less than 0.001) and quality of life (OR: 6.2; 95% CI: 1.6-13.1; P-value: less than 0.001). The control group exhibited poor health literacy (OR: 4.3; 95% CI: 1.3-7.7; P-value: 0.0033) and inadequate family support (OR: 4.1; 95% CI: 2.1-7.5; P-value: less than 0.001). Conclusion: As a conclusion, the findings of this study highlight the critical importance of implementing comprehensive strategies to address the issue of child marriage and the mental health repercussions that it can have. In order to effectively address the complex interaction of socioeconomic, cultural, and psychological variables that contribute to early marriage, these approaches need to prioritize prevention, intervention, and support services.